Effectiveness of a mobile, drop-in stop smoking service in reaching and supporting disadvantaged UK smokers to quit. Issue 1 (26th September 2014) - Venn, Andrea; Dickinson, Anne; Murray, Rachael; Jones, Laura; Li, Jinshuo; Parrott, Steve; McNeill, Ann
Abstract : Background: In countries where there are large disparities in smoking with persistent high rates among disadvantaged groups, there is a need to ensure that stop smoking services (SSS) reach such smokers. The primary aim of this study was to evaluate the effectiveness of a mobile, drop-in, community-based SSS in reaching more disadvantaged smokers, particularly those from routine and manual (RM) occupation groups, than standard services; secondary aims were to evaluate effectiveness in reaching those who had not previously accessed SSS, triggering unplanned quit behaviour, helping people quit and cost-effectiveness. Methods: Following a 4-week pilot period, a mobile drop-in SSS was delivered across various public locations in Nottingham City, UK for 6 months, offering behavioural and pharmacological support via one-to-one consultations with trained cessation advisors. Detailed demographic and smoking behaviour data were collected from all clients accessing the mobile SSS, and Nottingham's standard SSS for comparison. Results: Compared with smokers accessing the standard SSS (n=1856), mobile SSS smokers (n=811) were significantly more likely to be from the RM group (33.3% vs 27.2%, p=0.002), and to be first-time SSS users (67.8% vs 59.3%, p<0.001). Nearly 1 in 10 smokers setting a quit date through the mobile SSS had no prior quit intentions. The cost per smoker setting a quit date for the mobile SSS was only slightly higher than the standard SSS (£224 vs £202). Conclusions: A mobile drop-in SSS is an effective way of reaching more disadvantaged smokers from RM occupations, as well as those who have not previously accessed standard SSS and those without prior quit intentions.